2017
DOI: 10.1111/ijsa.12177
|View full text |Cite
|
Sign up to set email alerts
|

Rater training: Understanding effects of training content, practice ratings, and feedback

Abstract: Despite the popularity of frame‐of‐reference training (FORT), it is not clear how different structural elements of FORT work in concert to improve rating accuracy. Furthermore, past rater training studies have lacked rigorous control groups leading to low thresholds for showing improvements in rating accuracy due to FORT. The current study allowed for the isolation of components of rater training that increase rating accuracy when compared to a rigorously designed control group. Results indicated that repeated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…We should note that the FOR training seems to be effective, and it should be taken into account in future researches, especially in terms of increasing its effect on the accuracy of data provided by the SMEs, which occurs immediately after the presentation of the purpose and definitions of the dimensions rated by participants (Hauenstein & McCusker, 2017).…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%
“…We should note that the FOR training seems to be effective, and it should be taken into account in future researches, especially in terms of increasing its effect on the accuracy of data provided by the SMEs, which occurs immediately after the presentation of the purpose and definitions of the dimensions rated by participants (Hauenstein & McCusker, 2017).…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%
“…If the decisions that are made based on test results are vital, rater behaviors should be determined and these behaviors should be reduced to an acceptable level (Ellis et al, 2002). When the literature was examined, it was seen that many rater training designs were suggested and used (Bernardin & Buckley, 1981;Feldman et al, 2012;Haladyna, 1997;Hauenstein, & McCusker, 2017;Stamoulis & Hauenstein, 1993;Weigle, 1998;Zedeck & Cascio, 1982). When the literature is examined, it is seen that there are many rater trainings, but the existence of such a study in the national literature has been the main motivation for conducting this study.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have unearthed that rater effects are widespread and their effects can be mitigated by rater training and monitoring efforts (Feldman, Lazzara, Vanderbilt & DiazGranados, 2012;Hauenstein, & McCusker, 2017;Şata, 2019), and have demonstrated that many facet Rasch models (MFRM) can foster the detectability and understandability of the nature of these effects (Engelhard & Myford, 2003;Kim, Park & Kang, 2012;Wolfe, Chiu, & Myford, 2000).…”
Section: Introductionmentioning
confidence: 99%